Inmigrantes extranjeros y retornados en Galicia: la construcción del puente transnacional - Oso Casas, Laura; Golías Pérez, Montserrat; Villares Varela, María (Política y Sociedad, 2008)
Emigration has marked both the history and socioeconomic development of Galicia. Today however, it has undergone a series of changes in terms of its intensity, direction and “colour”. The presence of foreigners and the considerable numbers of first, second and third generation Galicians who opt to return to the region from America and Europe have turned Galicia into an object of study of the immigration phenomenon. This article is divided into various sections. In the first of these sections, secondary sources (the Municipal Population Census, Population and Housing Censuses, Active Workforce Surveys, etc.) are used to provide a socio-demographic analysis of the immigrant population in Galicia, in accordance with a range of variables including gender, age, country of origin and nationality, as well as labour and residential insertion. The second section describes the typology of immigration in Galicia based on migrants’ origin and nationality (returnees, dependent relatives of Galician emigrant returnees, foreign immigrants with no connections or ties with Galicia, autonomous descendents of Galician emigrants and transborder migrants). The third section describes the migratory projects of each type of migrant defined, as well as their strategies for labour and social incorporation. The final section analyses the migratory policy adopted by the Galician Autonomous Region.